A Randomized Trial on the Efficacy of Topical Estrogen vs. Vaginal Laser Therapy for Postmenopausal Vaginal Atrophy and Urinary Incontinence - Asma IhsanSidra ShafiqNishat AkramAqsa Tariq, Wajiha MehwishSaima Abid, Rahul Deb, Farah Naz Tahir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
A randomized controlled trial evaluated the efficacy of topical estrogen (TE) versus fractional CO₂ vaginal laser therapy (VLT) in treating postmenopausal vaginal atrophy (PVA) and urinary incontinence (UI). One hundred twenty postmenopausal women